Mucous Extravasation Phenomenon of Lingual Glands of Blandin and Nuhn - Rajalakshmi, R; Fathima, S Shabana; Sajeev, R (Journal of Orofacial Research, 2013)
Mucocele is a collection of mucin in the submucosa, which occurs mostly due to rupture of the gland proper or the duct of a minor salivary gland. They are most commonly found on the lower lip followed by floor of the mouth and buccal mucosa. Only 9 to 10% of Mucocele are found on the tongue and that they occur exclusively in the anterior lingual salivary glands of Blandin and Nuhn. The following is a case report of mucous extra-vasation phenomenon of lingual glands of Blandin and Nuhn.